PTU-058 Colon Capsule Endoscopy: A Useful Tool in the Diagnosis and Management of Inflammatory Bowel Disease. (17th August 2016) - Cook, JL; Hale, MF; Drew, K; Sidhu, R; McAlindon, ME
Abstract : Introduction: Colon capsule endoscopy (CCE) is a novel non-invasive means of directly imaging the colonic mucosal surface. Limited data is available regarding the utility of CCE in the diagnosis and re-assessment of inflammatory bowel disease (IBD), but it is attractive to patients due to its non-invasive nature and ability to obtain small bowel and pan-colonic images. We present a large series of patients with known or suspected IBD undergoing CCE. Methods: Retrospective, single-centre, including 193 patients with known or suspected IBD attending for CCE using PillCam Colon (Given Imaging, Israel). All patients known to have IBD successfully passed a PillCam Patency device prior. Demographical and procedural data was collated together with final diagnosis and management outcome. Results: Mean age 38.8 years (range 17–82), 129 female, median follow-up 43 months (range 3–99). 71 chose CCE over colonoscopy, 66 refused colonoscopy, 49 had an incomplete colonoscopy, and 7 were unfit for colonoscopy. Indication for the procedure: known IBD (n = 66, 5 with ulcerative colitis, 61 with Crohn's disease) of which 30 patients were undergoing CCE for disease re-assessment after 12 months of anti-TNF therapy and 36 due to a relapse in symptoms. The remaining 127 had suspected IBD. Procedure completion rate 75.5%, bowel preparation was good or adequate in 64.3%. There were no adverse events. In the known IBD group, 45 patients were diagnosed with active disease based on the CCE findings. This lead to changes in management in 44 patients (67%); mainly in the form of medication alteration (40 patients), but also by further investigation (4 patients). In the suspected IBD group, CCE diagnostic yield for IBD was 6%, 5 patients were diagnosed with Crohn's disease and 2 patients were diagnosed with ulcerative colitis. In the group with small bowel inflammation 1 patient was diagnosed with NSAID related enteropathy and 1 had non-specific histology and is undergoing further investigation. Other clinically relevant alternative findings are outlined in Table 1 . Overall CCE made 37 clinically significant diagnoses in the small bowel rather than the colon; 27 in the known IBD group and 10 in the suspected IBD group. Abbreviations: IBD=inflammatory bowel disease Conclusion: CCE is a useful patient friendly alternative for the diagnosis and re-assessment of patients with known or suspected IBD and impacts management. The distal small bowel is visualised with excellent clarity making CCE particularly useful for those with suspected or known ileocolonic disease. Disclosure of Interest: None Declared